Basics of Hypoglycemia - Raghav, Alok (IntechOpen, 2022)
Management of hypoglycemia in diabetes mellitus is a landmark achievement, especially in patients who take insulin. This book provides a comprehensive overview of hypoglycemia, including its pathophysiology, causes, clinical manifestations, management, and screening. It presents recent findings and research in the field and discusses new advancements in hypoglycemic control, including recently developed point-of-care devices for the home and the clinic.